Short communicationLeft circumflex coronary artery occlusion due to a left atrial appendage closure device - Katona, András; Temesvári, András; Szatmári, András; Nemes, Attila; Forster, Tamás; Fontos, Géza (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Nowadays, percutaneous left atrial appendage (LAA) closure is spreading, and a large number of patients with this procedure have concomitant coronary artery disease. With the presented case it could be concluded that coronary angiography is recommended before LAA closure.